A Generalized Reaction-Diffusion Epidemic Model with Time Delay - Lotfi, El Mehdi; Yafia, Radoune; Yousfi, Noura (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we propose a generalized reaction-diffusion epidemic model with time delay. The proposed model is governed by partial differential equations (PDEs). The global existence, positivity and boundedness of solutions are obtained. By analyzing the corresponding characteristic equation and constructing appropriate Lyapunov functionals, the local/global stability of homogeneous steady states are investigated. Finally, an application of our analytical results is given.